2019
DOI: 10.3390/sym11020292
|View full text |Cite
|
Sign up to set email alerts
|

Some General Classes of q-Starlike Functions Associated with the Janowski Functions

Abstract: By making use of the concept of basic (or q-) calculus, various families of q-extensions of starlike functions of order α in the open unit disk U were introduced and studied from many different viewpoints and perspectives. In this paper, we first investigate the relationship between various known classes of q-starlike functions that are associated with the Janowski functions. We then introduce and study a new subclass of q-starlike functions that involves the Janowski functions. We also derive seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 21 publications
(26 reference statements)
1
68
0
Order By: Relevance
“…This domain describes the conic type domain; for details, see [38]. Note that (i) When q → 1, then domain Ω κ,q (λ, α) reduces to the domain Ω κ (λ, α) (see [39]).…”
Section: Definition 1 ([35]mentioning
confidence: 99%
“…This domain describes the conic type domain; for details, see [38]. Note that (i) When q → 1, then domain Ω κ,q (λ, α) reduces to the domain Ω κ (λ, α) (see [39]).…”
Section: Definition 1 ([35]mentioning
confidence: 99%
“…In recent years, there is a great development of geometric function theory because of using quantum calculus approach. In particular, Srivastava et al [18] found distortion and radius of univalence and starlikenss for several subclasses of q-starlike functions with negative coefficients. They [19] also determined sufficient conditions and containment results for the different types of k-uniformly q-starlike functions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several interesting subclasses of analytic and multivalent functions have been introduced and investigated (see, for example, [9][10][11][12][13][14][15][16]). Motivated and inspired by recent and ongoing research, we introduce and investigate here a new subclass of close-to-convex functions in U which are associated with the lemniscate of Bernoulli by using some techniques similar to those that were used earlier by Sokół and Stankiewicz (see [3]).…”
Section: Introductionmentioning
confidence: 99%